El Cerrito : driving growth - Calkins, Tim; Karakkal, Jenn (London : SAGE Publications Ltd, 2017)
Michael Belden, longtime manager of the El Cerrito brand of high-end leather products and accessories, had just concluded a presentation to the senior executive team on his plan to increase profits by 4 percent over the next year. His new boss, Sara Jensen, was not pleased and instructed him to go back to the drawing board: You and I both know that a 4 percent profit increase just isnt sufficient. I was hoping to see an increase of 20 percent or more. Belden was deeply concerned. El Cerrito was a mature brand that catered to exclusive, high-end clientele. Would it be possible to generate the kind of growth Jensen wanted without damaging the brands equity?
Originally published: Calkins, T., & Karakkal, J. (2015). El Cerrito: Driving Growth. 5-414-756. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; El Cerrito; Business enterprises -- Growth; Business planning; Leather industry and trade